2007
DOI: 10.1186/1477-7800-4-21
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic granulomatous mastitis masquerading as carcinoma of the breast: a case report and review of the literature

Abstract: Background: Idiopathic granulomatous mastitis is an uncommon, benign entity with a diagnosis of exclusion. The typical clinical presentation of idiopathic granulomatous mastitis often mimics infection or malignancy. As a result, histopathological confirmation of idiopathic granulomatous mastitis combined with exclusion of infection, malignancy and other causes of granulomatous disease is absolutely necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 17 publications
3
56
1
10
Order By: Relevance
“…Bazen malignite benzeri klinik ve radyolojik bulgularla seyreden hastalığa şüpheli ince iğne aspirasyon biyopsisi sonuçları da eklenebilir. Literatürde bu şekilde gereksiz mastektomi yapı-lan İLGM olguları bildirilmiştir (11)(12)(13)(14). Bu durum meme karsinomu şüphelenilen hastalarda histopatolojik incelemenin önemini daha fazla arttırmaktadır.…”
Section: Olguunclassified
See 2 more Smart Citations
“…Bazen malignite benzeri klinik ve radyolojik bulgularla seyreden hastalığa şüpheli ince iğne aspirasyon biyopsisi sonuçları da eklenebilir. Literatürde bu şekilde gereksiz mastektomi yapı-lan İLGM olguları bildirilmiştir (11)(12)(13)(14). Bu durum meme karsinomu şüphelenilen hastalarda histopatolojik incelemenin önemini daha fazla arttırmaktadır.…”
Section: Olguunclassified
“…Bazen lezyonların etrafında psödokapsül oluşur. İnflamatuar proçes lobüler üniti destrükte ederek duktus boyunca ilerleyip duktus epitelinde ülserasyon ve yangısal hasara yol açabilir (8,(11)(12)(13)(14). Bu yazıda sunduğumuz 3. olgumuzda makroskopik olarak duktusa benzeyen tubuler uzantı halinde meme başına uzanım göste-ren inflamatuar intraduktal lezyon görülmektedir.…”
Section: Olguunclassified
See 1 more Smart Citation
“…Desde el informe de Kessler y Wolloch se han publicado más de 100 casos, la mayoría de ellos en mujeres de raza no caucásica (2) . El diagnóstico presuntivo, en algunos casos, fue de mastitis y, en otros, de cáncer mamario que condujo a la ablación innecesaria de la glándula mamaria (3) .…”
Section: Introductionunclassified
“…Although several studies have reported different approaches for the management of IGM, many of these treatment algorithms were formulated without a definitive initial diagnosis. 15 The treatment plan for IGM followed at most centres is to perform a complete resection or an open biopsy with corticosteroid therapy. 16 However, surgery can be complicated by abscess formation, fistulas, scarring and chronic suppuration.…”
mentioning
confidence: 99%